2022
DOI: 10.3390/cancers14071657
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics/Radiogenomics in Lung Cancer: Basic Principles and Initial Clinical Results

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide, and elucidation of its complicated pathobiology has been traditionally targeted by studies incorporating genomic as well other high-throughput approaches. Recently, a collection of methods used for cancer imaging, supplemented by quantitative aspects leading towards imaging biomarker assessment termed “radiomics”, has introduced a novel dimension in cancer research. Integration of genomics and radiomics approaches, where identifying the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Compared with previous radiogenomics studies, although our work overcame a few shortcomings, it still had some limitations ( 56 , 66 , 67 ). First, we used two radiogenomics cohorts of BC: one was a local single-center dataset for discovery ( n = 174) and another was a public multi-center dataset for validation ( n = 72).…”
Section: Discussionmentioning
confidence: 94%
“…Compared with previous radiogenomics studies, although our work overcame a few shortcomings, it still had some limitations ( 56 , 66 , 67 ). First, we used two radiogenomics cohorts of BC: one was a local single-center dataset for discovery ( n = 174) and another was a public multi-center dataset for validation ( n = 72).…”
Section: Discussionmentioning
confidence: 94%
“…Clinically important problems that have been addressed using radiomic analysis include (1) predicting patient prognosis in patients with lung cancers (2) predicting patients with lung cancer's response to therapy and which type of therapy is optimal (3) predicting whether lung tumours have certain molecular subtypes or genetic mutations, (4) predicting whether a pulmonary nodule is benign or malignant and requires biopsy. 8,[23][24][25] Recent studies have also shown that radiomic analysis of computed tomography (CT) scans of the chest can differentiate patients with coronavirus disease 2019 (COVID-19) from patients with other pneumonia of different aetiologies. [26][27][28] Radiomic analysis has been shown to predict (a) whether a patient who is positive for COVID-19 needs to be hospitalised (b) to predict whether a patient who is positive COVID-19 would need the intensive care unit (ICU) and/or ventilators [29][30][31] (c) how long a patient with COVID-19 is expected to be hospitalised (d) future mortality risk from COVID-19 and (e) predicting whether patients with COVID-19 go on to develop long COVID-19.…”
Section: External Validationmentioning
confidence: 99%
“…Initially, RF extraction was performed in neuroimaging, e.g., to achieve radiomic profiling of glioblastoma tissue to identify imaging predictors of patient survival and anti-angiogenic treatment response 218 , 219 . Many other studies have applied RF extraction to all types of tumors and imaging modalities, most prominently lung tumors 220 , often in combination with genomic profiling, termed radiogenomics 221 . In many cases, relevant RFs have been found to discriminate between different tumor classes, e.g., low- and high-grade gliomas 222 ; to be highly sensitive to cancerous tissue as in breast cancer 223 ; or to predict treatment response in prostate cancer 224 .…”
Section: Medical Image Computing In Translational Cancer Researchmentioning
confidence: 99%